CONTRIBUTION TO THE ISLAMIC RELIGIOUS EDUCATION FOR NATIONAL CHARACTER BUILDING: A LITERATURAL REVIEW - Khermarinah; Masrifa Hidayani (International Journal of Teaching and Learning, 2024)
In an era of globalization and rapid technological development, challenges to moral values and the character of nations are becoming increasingly complex. This raises an urgent need for education that not only prioritizes intellectual aspects but also focuses on character formation. In the Indonesian context, Islamic education plays an important role in meeting these needs, given the majority of its inhabitants who embrace Islam. This paper aims to investigate the contribution of Islamic religion education to the development of Indonesian character. The method of research carried out was literature, which examined various relevant sources to gain an in-depth understanding of how Islamic religious education contributed to shaping the values, attitudes, and behaviors expected of good citizens. This analysis includes research into Islamic education components such as curricula, teaching methods, the role of teachers and the educational environment, as well as their implementation in the daily lives of students. The results of the survey show that Islamic education has a significant effect in strengthening fundamental values such as honesty, justice, patience, tolerance, and caring for one another. Through integrated learning between theory and practice, Islamic education is able to form individuals not only qualified in academic aspects but also noble morality. In addition, Islamic education also plays a role in developing the social awareness and interpersonal skills of the students, which are important aspects in the development of the character of the nation.